2021
DOI: 10.1146/annurev-control-091420-084139
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Task and Motion Planning

Abstract: The problem of planning for a robot that operates in environments containing a large number of objects, taking actions to move itself through the world as well as to change the state of the objects, is known as task and motion planning (TAMP). TAMP problems contain elements of discrete task planning, discrete–continuous mathematical programming, and continuous motion planning and thus cannot be effectively addressed by any of these fields directly. In this article, we define a class of TAMP problems and survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
165
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 239 publications
(166 citation statements)
references
References 103 publications
1
165
0
Order By: Relevance
“…A planner must search over sequences of skills as well as parameter values that satisfy these constraints. Finding values that satisfy these constraints is a non-trivial problem; however, existing work in TAMP has shown that a variety of methods can be effective (Garrett et al, 2021). In this work we take a sampling-based approach using the PDDLStream TAMP planner (Garrett et al, 2020a), which we describe in Appendix B.…”
Section: Approachmentioning
confidence: 99%
“…A planner must search over sequences of skills as well as parameter values that satisfy these constraints. Finding values that satisfy these constraints is a non-trivial problem; however, existing work in TAMP has shown that a variety of methods can be effective (Garrett et al, 2021). In this work we take a sampling-based approach using the PDDLStream TAMP planner (Garrett et al, 2020a), which we describe in Appendix B.…”
Section: Approachmentioning
confidence: 99%
“…Perhaps the most relevant area of work to rearrangement planning is the field of task and motion planning (TAMP). TAMP is a broad area of study that looks at integrating discrete high-level planning (which objects to grab, which actions to execute) with continuous low level planning (which positions in which to place objects) [7]. This area generally relies on model-based methods, using known objects and fully-observable domains, although work has been done to weaken these assumptions, particularly in recent years.…”
Section: Related Workmentioning
confidence: 99%
“…Rearrangement planning is a common subset of task and motion planning [3,15,21,16,7]. It has recently been identified as an interesting challenge area for robotics research [1].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper serves as a guideline for navigating the landscape of existing solutions and their caveats when designing combined task and motion planning methods. As opposed to the latest survey on this topic (Garrett et al, 2020), we here analyze a wider scope of concerns within TAMP and their combination; in particular, we discuss several orthogonal aspects, including uncertainty handling and online planning. Also, the discussion is centered on five open research questions and how answering them matters in a selection of industrially-relevant application contexts.…”
Section: Introductionmentioning
confidence: 99%